PEMETAAN DISPARITAS DAN POTENSI EKONOMI KABUPATEN/KOTA DI JAWA BARAT: PENDEKATAN TIPOLOGI KLASSEN 2016-2023 - Hidayatullah, Nur; Sumitro, Sutyastie (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
Development disparities in West Java continue to widen every year. In this context, it is crucial to analyze the factors contributing to these disparities, including the roles of different economic sectors across regions. This study aims to classify regions and economic sectors into advanced, developing, potential, and underdeveloped categories, enabling policymakers to formulate targeted policies to enhance Gross Regional Domestic Product (GRDP). The study employs the Klassen Typology Analysis at both regional and sectoral levels in West Java Province. The data used include Economic Growth Rates and GRDP at constant prices, as well as per capita GRDP, sourced from publications by the West Java Central Statistics Agency (BPS). In addition, data on sectoral growth and sectoral contributions to GRDP were obtained from GRDP publications by business field from individual BPS offices in districts and cities across West Java. The analysis reveals that five regions are categorized as rapidly advancing and fast-growing areas, while ten regions fall into the category of rapidly developing areas. Three regions are classified as advanced but stagnant, and eight regions are categorized as underdeveloped. In addition, there are significant economic variations across regions. The primary sector dominates agricultural areas such as Ciamis, Garut, and Pangandaran, whereas the secondary sector thrives in industrial hubs like Bandung Regency and Karawang. Several cities, including Bandung and Cimahi, are shifting their focus toward the tertiary sector due to urbanization and the growth of services and trade. However, some regions still face challenges, including stagnation in the primary sector as a result of industrialization and limited infrastructure that constrains the growth of the secondary sector.